2019
DOI: 10.3390/insects10040085
|View full text |Cite
|
Sign up to set email alerts
|

Habrobracon hebetor and Pteromalus cerealellae as Tools in Post-Harvest Integrated Pest Management

Abstract: Consumers are increasingly demanding pesticide-free grain/legumes and processed foods. Additionally, there are more restrictions, or complete loss, of insecticides labelled for use in managing stored grain insects in post-harvest ecosystems. Suppression of post-harvest pests using parasitic wasps is a more sustainable alternative than chemical pesticides. Habrobracon hebetor (Say) (Hymenoptera: Braconidae) and Pteromalus cerealellae Ashmead (Hymenoptera: Pteromalidae) are two important parasitoids that limit e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 74 publications
1
19
0
1
Order By: Relevance
“…The Braconidae wasp, Habrobracon ( Bracon ) hebetor (Hymenoptera: Braconidae) is a cosmopolitan, gregarious, koinobiont, synovigenic, 5, 8 and highly polyphagous ectoparasitoid, which attacks the late larval stage of several species of pyralid and noctuid moths 4, 7, 9 . It is one of the most promising biocontrol agents for pyralid moths of stored products due to its short pre‐adult period, high reproduction capacity, and high parasitism rate 8 . H. hebetor females first paralyze their hosts by injecting venom through the host cuticle with their ovipositor; thereafter, they deposit a variable number of eggs on or near the surface of the selected hosts (immobilized larvae) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Braconidae wasp, Habrobracon ( Bracon ) hebetor (Hymenoptera: Braconidae) is a cosmopolitan, gregarious, koinobiont, synovigenic, 5, 8 and highly polyphagous ectoparasitoid, which attacks the late larval stage of several species of pyralid and noctuid moths 4, 7, 9 . It is one of the most promising biocontrol agents for pyralid moths of stored products due to its short pre‐adult period, high reproduction capacity, and high parasitism rate 8 . H. hebetor females first paralyze their hosts by injecting venom through the host cuticle with their ovipositor; thereafter, they deposit a variable number of eggs on or near the surface of the selected hosts (immobilized larvae) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…4 They have been widely used as important integrated pest management tools to control stored product pests 5,6 ; however, research on the biological control of E. elutella is still lacking. 7 The Braconidae wasp, Habrobracon (Bracon) hebetor (Hymenoptera: Braconidae) is a cosmopolitan, gregarious, koinobiont, synovigenic, 5,8 and highly polyphagous ectoparasitoid, which attacks the late larval stage of several species of pyralid and noctuid moths. 4,7,9 It is one of the most promising biocontrol agents for pyralid moths of stored products due to its short preadult period, high reproduction capacity, and high parasitism rate.…”
Section: Introductionmentioning
confidence: 99%
“…Cyfluthrin was the most toxic one which was dangerous on all life stages of B. hebetor, influencing the number of laid eggs by the parasitoid and percent of pupation and leading to failure of adult emergence. Mbata and Warsi (2019) performances of H. hebetor depend on a wide range of factors, such as host species, commodities, and environmental conditions. The result of the tested enzymes agrees with Kandil et al (2013a, b) who found that the chlorfluazuron caused high reduction in total lipid, protein, and carbohydrates in full-grown larvae of P. gossypiella, and Said et al (2017) recorded that IGRs caused high difference in the total protein and lipid for P. gossypiella larvae than the control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the last two decades, resistance to specific chemicals has been recorded for more than 504 pest species, including many stored product insect pests [ 3 , 4 ], reducing the effectiveness of pesticide treatments. Thus, the development of alternative approaches for pest control is a key issue to address the increasing market demand for pesticide and insect-free food, as well as to face the shortage of food commodities in many countries worldwide [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%